Homologs of bacterial heat-labile enterotoxin subunit A contribute to development, stress response, and virulence in filamentous entomopathogenic fungus Beauveria bassiana - Ding, Jin-Li; Wei, Kang; Feng, Ming-Guang; Ying, Sheng-Hua (Frontiers in Immunology, 2023)
Enterotoxigenic bacteria commonly excrete heat-labile enterotoxins (LT) as virulence factors which consist of one subunit A (LTA) and five B subunits (LTB). In fungi, there are a large number of genes encoding the homologs of LTA, but their biological roles remain largely unknown. In this study, we identified fourteen enterotoxin_A domain proteins in filamentous fungus B. bassiana in which five proteins were functionally characterized. Five proteins displayed diverse sub-cellular localizations, but perform convergent functions in stress response, development, and virulence. The loss of five LTA genes resulted in significant reduction in conidial production, blastospore formation, and the increased sensitivity to oxidative and cell-wall perturbing stresses. The virulence of five disruptants was notably weakened as indicated by topical and intrahemocoel injection assays. Notably, the loss of these five proteins led to the significant changes in the carbohydrate profiles of cellular surface, which induced the enhanced host immune reactions of encapsulation and melanization. Thus, LTA proteins contribute to the fungus-host interaction via maintaining the carbohydrate profiles of cellular surface. This study expends our understanding of the enterotoxin_A domain proteins in fungal physiology and deepens mechanisms involved in the lifestyle of fungal insect pathogens.